#TITLE_ALTERNATIVE# - CAHYA WIDIYANTI (NIM:10209081), SEPTI
Magnetotelluric method is a geophysical method that aims to determine the resistivity structure of the subsurface sounding principles, is passive, and using the natural electromagnetic fields. The results obtained are sounding curve resistivity against frequency curve. This curve illustrates the distribution of resistivity values at certain depths. In measuring, curves in the TE mode and TM mode are often not as expected. It required the analysis of one of the causes that static effect. The static effects of resistivity structure is made with 2D forward modeling using finite difference method.